Institutional complexity in professional service firms and dysfunctional behaviors: Evidence from a multi-country study - Pruijssers, Jorien (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
In most organizational fields, multiple and sometimes conflicting institutional logics coexist, a phenomenon termed institutional complexity. Its behavioral implications have only recently been studied. This study analyzes how sustained institutional complexity through organizational design influences individual dysfunctional behavior. It is posited that organizations sustaining institutional complexity through their organizational designs provide structural assurance that may legitimize behavior that deviates from norms. These claims are tested through a field study in the accounting industry across three countries. It reveals that the perceived presence of institutional complexity can stimulate perceived dysfunctional behaviors. By considering the interplay of institutional complexity and individual dysfunctional behavior, the research unveils unintended consequences of sustained institutional complexity, offering a fresh perspective on sustained institutional complexity.